Trusting Reusable Business Components in a Service-Oriented Architecture a visible quality process is key. - Ariola, Wayne
One of the business benefits organizations strive to achieve by implementing a service-oriented architecture (SOA) or in utilizing Web services is the opportunity to reuse business components. Asset reuse is one of the core drivers of the SOA or Web service ROI calculation. Although leveraging the service concept provides an avenue for application consolidation and reuse, these same efficiencies also introduce a distinct level of business risk.